Suicidality in People With Obsessive-Compulsive Symptoms or Personality Traits - Bowen, Rudy; Rahman, Hiba; Dong, Lisa Yue; Khalaj, Sara; Baetz, Marilyn; Peters, Evyn; Balbuena, Lloyd (Frontiers in Psychiatry, 2019)
Objective: Obsessive-Compulsive Disorder (OCD) and Obsessive-Compulsive Personality Disorder (OCPD) have been reported to be associated with mood instability (MI), depression and the spectrum of suicidality. We examined whether OCD and OCPD, and obsessional thoughts of death, are associated with suicidal thoughts, non-suicidal self-injury and attempted suicide. Methods: We used data from the 2000 British Adult Psychiatric Morbidity survey that elicited symptoms of OCD with a computerized version of the CIS-R and traits of OCPD with a self-completed version of the SCID-II. We created a series of logistic regression models, first entering only OCD and OCPD traits in separate models, to which depression and mood instability (MI) were added. We also examined the relation of obsessional thoughts about death with self-harm in a network analysis model that included the main symptoms of mood instability and depression. Results: Both OCD and OCPD were significantly associated with suicidal thoughts, and suicidal actions. Only OCPD was associated with non-suicidal self-injury. Depression and MI are both predictors of all three self-harm outcomes. In the network analysis, MI bridged depressive symptoms with self-harm. Obsessions and compulsions connected to self-harm through MI. Conclusions: The total burden of OCD and OCPD is responsible for the association of OCD and OCPD and suicidal thoughts, rather than thoughts of death or harm alone. The association of MI and depression with thoughts and actions of self-harm is confirmed.